ANALISIS KESEJAHTERAAN PETANI GAMBIR DAN KARET DI KECAMATAN KAPUR IX - Jefri Anfal; Febriandi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Farmers' welfare can be seen from the ability to fulfill basic needs (clothing, shelter, food), education, and income. The level of family welfare is divided into 5 stages. This study uses a quantitative method. The population of this study was 6,032 farmers. The total sample used in this study was 98 farmers consisting of 68 gambier farmers and 30 rubber farmers. Data collection used a questionnaire. The results of data collection were analyzed using the TCR (Respondent Achievement Level) technique. The ability to fulfill basic needs, gambier farmers got a score of 88 categorized as capable, while rubber farmers got a score of 72 categorized as quite capable. The educational indicator of respondents' achievement scores for gambier farmers was 86 with a good category, while for rubber farmers the respondent's achievement score was 70 with a less good category. The average income of gambier farmers is higher than the average income of rubber farmers. The results of the analysis of farmer welfare level data referring to welfare indicators from the National Population and Family Planning Board (BKKBN), gambier farmers in Kapur IX District are more prosperous than rubber farmers. The Sig. (2-tailed) value on the ability to fulfill basic needs, education and income is 0.000 < 0.05, so it can be concluded that there is a difference between the welfare of gambier farmers and the welfare of rubber farmers in Kapur IX District in terms of income.